MRI and CT in the follow-up after irreversible electroporation of small renal masses - Buijs, Mara; de Bruin, Daniel Martijn; Wagstaff, Peter G. K.; Zondervan, Patricia J.; Scheltema, Matthijs J., V.; Engelbrecht, Marc; del Pilar Laguna Pes, Maria; van Lienden, Krijn P. (Turkish Society of Radiology, 2021)
PURPOSE Ablation plays a growing role in the treatment of small renal masses (SRMs) due to its nephron sparing properties and low invasiveness. Irreversible electroporation (IRE) has the potential, although still experimental, to overcome current limitations of thermal ablation. No prospective imaging studies exist of the ablation zone in the follow-up after renal IRE in humans. Objectives are to assess the use of computed tomography (CT) and magnetic resonance imaging (MRI) to determine the ablation zone volume (AZV), enhancement and imaging characteristics after renal IRE. METHODS This was a prospective phase 2 study of IRE in 9 patients with 10 SRMs. MRI was performed pre-IRE, 1 week, 3 months, 6 months, and 12 months after IRE. CT was performed pre-IRE, perioperatively (direct after ablation), 3 months, 6 months, and 12 months after IRE. AZVs were assessed by two independent observers. Observer variation was analyzed. Evolution of AZVs, and their relation with the needle configuration volume (NCV; indicating planned AZV) were evaluated based on CT and MRI measurements. RESULTS Eight SRMs were clear cell renal cell carcinomas, one SRM was a papillary renal cell carcinoma and one patient had a nondiagnostic biopsy. On CT, median AZV increased perioperatively until 3 months post-IRE (16.8 cm(3) and 6.2 cm(3), respectively) compared with the NCV (4.8 cm(3)). On MRI, median AZV increased 1 week post-IRE until 3 months post-IRE (14.5 cm(3) and 4.6 cm(3), respectively) compared with the NCV (4.8 cm3). At 6 months the AZV starts decreasing (CT 4.8 cm(3); MRI 3.0 cm(3)), continuing at 12 months (CT 4.2 cm(3), MRI 1.1 cm(3)). Strong correlation was demonstrated between the planned and the post-treatment volumes. Inter-observer agreement was excellent (CT: 95% CI 0.82-0.95; MRI: 95% CI 0.86-0.96). All SRMs appeared non-enhanced immediately after ablation, except for one residual tumor. Subtraction images confirmed non-enhancement on MRI in cases with unclear enhancement (3/9). Directly after IRE, gas bubbles, perinephric stranding, and edema were observed in all cases. CONCLUSION Both CT and MRI findings indicate increase of AZV until 3 months post-IRE, followed by gradual decrease in AZV from 6 to 12 months post-IRE. Enhancement is absent in cases with complete ablation. Gas bubbles, perinephric stranding, and edema are normal findings directly post-IRE.
Keywords: MRI; CT; Renal Masses; Electroporation